ANALISIS PARAMETER KEKUATAN GESER ANTARMUKA PASIR PALANGKARAYA - GEOTEKSTIL - -, Fathurrozi (INTEKNA informasi teknik dan niaga, 2014)
Soil reinforcement using geo-textile is one of geotechnical structures, involving soil-structureinteraction. Recently, the problems are solved by neglecting the interface influencebetween soil and structure. To obtain more realistic shear-strength parameter, it is requiredto study the soil-structure interface. The study of behavior of soil-geotextile interactionon the shear strength parameters is discussed in this research. The used soils in this researchare Palangkaraya sand. The well graded sand has relative density of 90%. Thesand sample is based on the maximum dry density (MDD) value obtained from standardVibrating table test ASTM D 4253. Determination of interface parameter on the shearstrength of sand geo-textile is obtained from direct shear test ASTM 3080. The intrinsicinterface shear strength parameters are friction angle of interface interface (?). The usedinterface types are woven, non-woven and reinforcement. Result of the research givesreview on the behavior and interface modeling of soil-geotextile. Values of friction angle ofinterface (?) obtained from sand-non-woven geotextile are higher than sand- wovengeotextile. The value of ? obtained from sand reinforcement is the highest. Ratio of ?/? fornon-woven geotextile ranges between 0,89~0.93. Ratio of ?/? for woven geotextile is about0.81~0.87. Reinforcement ratio of ?/? is about 0.96 ~ 0.97. The value of ?/? is relativelyconstant at residual strength conditions. The interface shear strength parame-ters areinfluenced by the roughness of material. Nominal mass, tensile strength and elo-ngation isslightly given influenced concerning shear strength interface parameters. The efficiency asthe portion of soil shear strength parameters that is mobilized showing trend are similar to ?and ?/?. The result of this research can give contribution on determina-tion of interfaceshear strength parameters in the analysis of soil reinforcement using geotextile in order todesign optimalization.